What we actually know about the pathogenicity of Bacteroides pyogenes - Majewska, Anna (Med Microbiol Immunol, 2021)
The aim of the study was to evaluate the pathogenic potential of Bacteroides pyogenes, rarely identified in clinical laboratories anaerobic bacteria. To increase the knowledge about this poorly understood anaerobic microorganism, the study also includes cases of infections described so far in the literature. Only the use of 16S rRNA sequencing and mass spectrometry technique allowed the identification of B. pyogenes from clinical specimens. We reported 13 severe human infections caused by B. pyogenes. Bacteria were cultured from the wound after biting by animals, chronic infections within the oral cavity, from patients with histologically or radiological proven osteomyelitis, surgical site infection, and from urine sample collected after a urological procedure. Most (9/13) of the patients required hospitalization. Almost 70% of them needed urgent admission via the emergency room. Two inpatients due to a life-threatening condition were admitted to the intensive care unit. Almost 50% of isolates were resistant to penicillin. All resistant to penicillin strains were isolated from skin and mucous membrane infections.